2006
DOI: 10.1103/physrevd.74.056004
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetry andCPviolation in|ΔS|=1τdecays

Abstract: We compute the SUSY effective hamiltonian that describes the |∆S| = 1 semileptonic decays of tau leptons. We provide analytical expressions for supersymmetric contribution to τ → usν τ transition in mass insertion approximation. We show that SUSY contributions may enhance the CP asymmetry of τ → Kπν τ decays by several orders of magnitude than the standard model expectations. However, the resulting asymmetry is still well below the current experimental limits obtained by CLEO collaborations. We emphasize that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…24 A similar upper limit was set in Ref. [90] in the context of SUSY contributions to this observable. The recent paper [91] finds that a charged Higgs contribution can enhance CP violation in the K ± π 0 tau decays modes up to A CP 2 × 10 −6 , which is much larger than the corresponding (negligible) SM contribution [38].…”
Section: Discussionmentioning
confidence: 95%
“…24 A similar upper limit was set in Ref. [90] in the context of SUSY contributions to this observable. The recent paper [91] finds that a charged Higgs contribution can enhance CP violation in the K ± π 0 tau decays modes up to A CP 2 × 10 −6 , which is much larger than the corresponding (negligible) SM contribution [38].…”
Section: Discussionmentioning
confidence: 95%
“…Three-, four-and five-body FS have two, three and four hadrons π, K and/or η. One can probe the complex FS with independent of τ production asymmetry [10,11,12,13].…”
Section: Landscape For τ Decaysmentioning
confidence: 99%
“…The CP asymmetry in the decay mode τ ± → K ± π 0 ν τ , in minimal supersymmetric extension of the SM with R parity conservation, has been computed in Ref. [2]. It was shown that the SUSY contributions can enhance the CP asymmetry rate in τ -decay by many order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The effective Hamiltonian H ef f derived from SUSY superpotential with R parity symmetry conserved can be expressed as [2]…”
Section: Introductionmentioning
confidence: 99%